Kebijakan Luar Negeri Indonesia Era Presiden Jokowi Dalam Penyelesaian Krisis Kemanusiaan Di Rohingya Tahun 2014-2019 - Ilham Falahul Alam; Adi Joko Purwanto (Kajian Hubungan Internasional, 2021)
This thesis aims to analyze Indonesia's foreign policy in the era of President Jokowi in resolving the humanitarian crisis in the Rohingya from 2014 to 2019. This research is based on the ethnic conflict that occurred in Myanmar, namely between the Rohingya ethnicity who is predominantly Muslim and the Rakhine ethnic Buddhist. does not recognize the population of the Rohingya minority living in Rakhine as citizens of Myanmar because they do not have a clear identity and are considered refugees. This problem has been going on for years because the problem is very complex. This research was written using qualitative descriptive writing techniques, and the data obtained were not directly from the object of the field research. Researchers get data from existing literature such as books, journals, articles, news. By using the perspective of Kegley and Wittkopf that in making foreign policy using the rational choice model, there are four steps that must be followed by policy makers, namely Problem Recognition and Definition, Goal Selection, Identification of Alternatives, and Choice. The result of this research is that the Government of Indonesia takes a decision which considers the costs and benefits of the national interest. In the end, Indonesia adopted a policy of providing humanitarian assistance, a policy of assistance to refugees, a policy of carrying out Indonesia's bilateral diplomacy towards Myanmar.